Verifying critical cyber-physical systems after deployment - O'Halloran, C (European Association of Software Science and Technology, 2015)
Cyber-Physical Systems (CPS) are increasingly novel hardware and software compositions creating smart, autonomously acting devices, enabling efficient end-to-end workflows and new forms of user-machine interaction. The heterogeneous, evolving and distributed nature of CPS means that there is little chance of performing a top down development or anticipating all critical requirements such devices will need to satisfy individually and collectively. This paper describes an approach to verifying system requirements, when they become known, by performing an automated refinement check of its composed components abstracted from the actual implementation. This work was sponsored by the Charles Stark Draper Laboratories under the DARPA HACMS project.